1993
DOI: 10.1002/etc.5620121207
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical processes affecting selenium cycling in wetlands

Abstract: -Important selenium data in the literature are discussed with reference to the biogeochemical processes affecting selenium cycling in wetlands. Selenium oxidation-reduction reactions are shown to be the most important biogeochemical processes controlling speciation, precipitation/ dissolution, sorption/desorption, methylation, and volatilization of selenium. Furthermore, bioavailability and toxicity of selenium, with reference to wetland ecosystems, are summarized. Based on the information available in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…In a study on Se(VI) reduction to Se(0) in a water–sediment system, Tokunaga et al (1996) found that 60% of the newly formed Se(0) in sediment during an experiment was reoxidized to Se(IV) and Se(VI) at Day 2 after collection. In a flooded sediment system at pH 7, Masscheleyn and Patrick (1993) reported that the boundary between Se(VI) and Se(IV) is at an Eh of about 250 to 285 mV, and between Se(IV) and Se(0), at an Eh of about −10 to −40 mV. In this study, the redox potential in the water column and water–sediment system increased during the experiments (Fig.…”
Section: Resultssupporting
confidence: 57%
“…In a study on Se(VI) reduction to Se(0) in a water–sediment system, Tokunaga et al (1996) found that 60% of the newly formed Se(0) in sediment during an experiment was reoxidized to Se(IV) and Se(VI) at Day 2 after collection. In a flooded sediment system at pH 7, Masscheleyn and Patrick (1993) reported that the boundary between Se(VI) and Se(IV) is at an Eh of about 250 to 285 mV, and between Se(IV) and Se(0), at an Eh of about −10 to −40 mV. In this study, the redox potential in the water column and water–sediment system increased during the experiments (Fig.…”
Section: Resultssupporting
confidence: 57%
“…Rapid sequence reduction of Se(VI) to Se(0) can also be explained by the redox potential of the rice straw solution. Masscheleyn and Patrick (1993) reported that a sequence reduction from Se(VI) to Se(IV) and then to Se(0) at a given pH was related to the redox potential. In a flooded sediment system at pH 7, Se(VI) reduced to Se(IV) at a redox potential of 250 to 285 mV, and Se(IV) reduced to Se(0) at redox potentials of −10 to −40 mV (Masscheleyn and Patrick, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Masscheleyn and Patrick (1993) reported that a sequence reduction from Se(VI) to Se(IV) and then to Se(0) at a given pH was related to the redox potential. In a flooded sediment system at pH 7, Se(VI) reduced to Se(IV) at a redox potential of 250 to 285 mV, and Se(IV) reduced to Se(0) at redox potentials of −10 to −40 mV (Masscheleyn and Patrick, 1993). In this study, the redox potential in the rice straw solution dropped rapidly to levels that were much lower than −40 mV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At low levels of redox potential in drainage water, bacteria reduced NO − 3 and Se(VI) effectively. Nitrate is a competitive electron acceptor affecting Se(VI) reduction because of its similar redox potential in aquatic systems (Masscheleyn and Patrick, 1993). In a batch study on the effect of NO − 3 on Se(VI) reduction to Se(0) in drainage water by rice straw, Zhang and Frankenberger (2003b) found that a level of 100 mg L −1 of NO − 3 in drainage water had little effect on Se(VI) reduction to Se(0).…”
Section: Discussionmentioning
confidence: 99%